The Role of Satellite DNAs in Genome Architecture and Sex Chromosome Evolution in Crambidae Moths - Cabral-de-Mello, Diogo C.; Zrzavá, Magda; Kubíčková, Svatava; Rendón, Pedro; Marec, František (Frontiers in Genetics, 2021)
Tandem repeats are important parts of eukaryotic genomes being crucial e.g. for centromere and telomere function and chromatin modulation. In Lepidoptera, knowledge of tandem repeats is very limited despite the growing number of sequenced genomes. Here we introduce seven new satellite DNAs (satDNAs), which more than doubles the number of currently known lepidopteran satDNAs. The satDNAs were identified in genomes of three species of Crambidae moths, namely Ostrinia nubilalis, Cydalima perspectalis, and Diatraea postlineella, using graph-based computational pipeline RepeatExplorer. These repeats varied in their abundance and showed high variability within and between species, although some degree of conservation was noted. The satDNAs showed a scattered distribution, often on both autosomes and sex chromosomes, with the exception of both satellites in D. postlineella, in which the satDNAs were located at a single autosomal locus. Three satDNAs were abundant on the W chromosomes of O. nubilalis and C. perspectalis, thus contributing to their differentiation from the Z chromosomes. To provide background for the in-situ localization of the satDNAs, we performed a detailed cytogenetic analysis of the karyotypes of all three species. This comparative analysis revealed differences in chromosome number, number and location of rDNA clusters, and molecular differentiation of sex chromosomes.